Victimization and perpetration of intimate partner violence among female and male youth and adults in South Africa - Peltzer, Karl; Phaswana-Mafuya, Nancy; Pengpid, Supa (Global Journal of Health Science, 2017)
Objective: Intimate partner violence (IPV) is a huge public health problem. The aim of the study was to estimate the prevalence and influence of sociodemographic and health characteristics on IPV victimization and perpetration among women and men 15 years and older in South Africa. Materials and Methods: Data based on the South African national population-based survey in 2012 for 15916 (8532 women and 7384 men) aged 15 years and older who were in an intimate partner relationship were analysed. Bivariate and multivariable logistic regression was conducted to assess the association between sociodemographic factors, health variables and IPV victimization and perpetration. Results: Among women, 8.5% had experienced any form of IPV in the past 12 months, and 3.5% of the women had engaged in IPV perpetration in the past 12 months. Among men, 5.0% had experienced any form of IPV in past 12 months, and 4.4% of the men had engaged in IPV perpetration in the past 12 months. In multivariable logistic regression analysis among women, younger age, being African Black, having psychological distress, having been a victim of violent crime and having had multiple sexual partners were associated with IPV victimization in the past 12 months, while younger age, psychological distress, hazardous or harmful alcohol use, and having had multiple sexual partners was associated with IPV perpetration in the past 12 months. In multivariable logistic regression analysis among men, younger age, psychological distress, hazardous or harmful alcohol use, and having been a victim of violence crime was associated with IPV victimization in the past 12 months, while younger age, poor health status, psychological distress, hazardous or harmful alcohol use, and illicit drug use was associated with IPV perpetration in the past 12 months. Conclusion: Past 12-month prevalence of IPV victimization and perpetration among women and men was significant. IPV gender commonalities and differences in risk factors, such as psychological distress, substance use, crime victimization and sexual risk behaviour, may inform strategies of violence prevention programmes.
Journal article published in the Global Journal of Health Science; Vol. 9, No. 10; 2017 Published by Canadian Center of Science and Education
Keywords: Intimate partner violence; victimization; perpetration; women; men; risk factor; South Africa; national survey; Public health; Dating violence; Intimate partner violence; Prison violence